Why Collect Science? - Samuel J M M Alberti (Journal of Conservation and Museum Studies, 2017)
In this critical assessment of the ‘museology of science’ I cherry-pick recent scholarship and practice to unpack the functions of science collections. Some practices (exhibition, engagement, study) have already attracted considerable attention, others not yet (storage); but all tend to be considered separately as case studies from particular institutions and for particular disciplinary audiences. Juxtaposing different reasons to collect reveals both the tensions inherent in science collections and the opportunities these collections afford, especially around their materiality. This is why we have collected science, and why we should continue.